The features and aetiology of Fournier's gangrene. - Efem, S. E. (BMJ Group, 1994)
This paper reports a clinical study of 20 cases of gangrenous ulcers of the scrotum and/or of the penis (Fournier's gangrene) and a review of previous publications. Even though found mostly in elderly male patients, the disease spares no age group and can involve the external genitalia in neonates and women as well. The disease is a necrotising fasciitis of infective origin and always has a portal of entry of the infecting organisms even though it may be so trivial as to be undetected. The commonest portals of entry of infection are periurethral sepsis, groin wound sepsis, anorectal sepsis, prostatic sepsis and trauma. The infecting organisms comprise both aerobic and anaerobic organisms such as Escherichia coli, Streptococcus pyogenes, Pseudomonas aeruginosa, Klebsiella pneumonia, Proteus mirabilis, enterococci, Bacteroides fragilis and anaerobic streptococcus. Fournier's gangrene is probably the same disease as necrotizing fasciitis occurring in other parts of the body, but modified by the peculiar anatomy of the genitoperineum.